In vitro antibacterial activity of traditionally used medicinal plants against Xanthomonas campestris pv. musacearum in Ethiopia - GETAHUN YEMATA; BRUKTAWIT DESTA; MASRESHA FETENE (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yemata G, Desta B, Fetene M. 2019. In vitro antibacterial activity of traditionally used medicinal plants against Xanthomonas campestris pv. musacearum in Ethiopia. Biodiversitas 20: 555-561. In Ethiopia, traditional medicinal plants have long been used to treat human and livestock ailments. Nevertheless, studies about the use of these plant extracts to control crop diseases are scarce. Therefore, the aim of the present study was to evaluate the antibacterial activity of traditionally used medicinal plants against Xanthomonas campestris pv. musacearum (Xcm). The bioactive chemicals from leaf samples were drawn using methanol by maceration method. Total phenolic content of the extracts was determined by Folin Ciocalteau reagent. The antibacterial activity of leaf extracts was evaluated by disc diffusion method. The phytochemical analysis revealed the presence of alkaloids, flavonoids, phenolic compounds, terpenoids, tannins and saponins. Extracts with higher total phenolic content had greater antibacterial activity. The extract of each species showed antibacterial activity against Xcm on a dose dependent manner. Significant differences were recorded between species and test concentrations. The extract of Bersama abyssinica exhibited the strongest antibacterial activity at 200 mg/mL followed by Ricinus communis, Eucalyptus citriodora and Acokanthera schimperi. At lower test concentrations, extracts of E. citriodora and R. communis revealed higher antibacterial activity. Moreover, these species had lower bacteriostatic and bactericidal concentrations. The results showed the potential potency of E. citriodora and R. communis leaf extracts in controlling enset bacterial wilt. However, further studies on the identification of chemical compounds and in vivo evaluation of the extracts are recommended.